AI driven automation for enhancing sustainability efforts in CDP report analysis - Ramya Rangarajan; Tamilarasi Kathirvel Murugan; Logeswari Govindaraj; Venyaa Venkataraman; Krithik Shankar (Scientific Reports)
Abstract The need for sustainable practices in supply chains is becoming increasingly critical, as businesses face pressure to reduce their carbon footprint while maintaining operational efficiency. This paper proposes a novel hybrid approach that combines Genetic Algorithms (GA) with Long Short-Term Memory (LSTM) networks to optimize supply chain sustainability. The proposed system leverages publicly available Carbon Disclosure Project (CDP)-reported data to predict emissions and optimize resource allocation. The primary objective of this research is to develop a cost-effective, scalable solution that reduces emissions, improves operational efficiency, and ensures regulatory compliance within supply chains. The hybrid model consists of two main components: LSTM networks for predictive modeling of emission trends and GA for optimization of supply chain processes. LSTM is used to forecast future emissions based on historical data, while GA optimizes resource management, including transportation choices and energy consumption, to minimize emissions and operational costs. The system employs a multi-objective optimization approach, addressing the simultaneous goals of emission reduction, operational efficiency, and compliance with environmental regulations. The experimental results demonstrate the effectiveness of the proposed approach. A 23.67% reduction in total emissions was achieved, with the most significant improvements in indirect emissions. The system also improved operational efficiency by 10.98%, while ensuring 100% compliance with environmental regulations, eliminating any penalties. The hybrid GA-LSTM framework offers valuable insights for businesses seeking to meet sustainability targets and provides a practical, data-driven method for improving supply chain performance. The proposed system is not only applicable to large corporations but can also be scaled for use in small and medium-sized enterprises, offering a pathway for widespread adoption of sustainable practices across industries.